Field research 2010 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2010)
Includes research reports from these locations: East Central Kansas Experiment Field, Kansas River Valley Experiment Field, South Central Kansas Experiment Field, and Western Kansas Agricultural Research Centers.
Keywords: Kansas Agricultural Experiment Station contribution; no.10-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1030; Kansas; Agriculture; Crops; Weed control; Disease control; Fertilizer; Irrigation